The Effect of Android Application-Based Counseling on The Knowledge of Mothers of Toddlers Related to Complementary Feeding - Hikmah, Atiq Dzul (Sport and Nutrition Journal, 2023)
Malnutrition is a serious health problem with a high prevalence in Indonesia and must be addressed immediately. Mother's knowledge of complementary foods can affect the nutritional intake of toddlers. This indirectly affects the nutritional status of toddlers. Lack of maternal knowledge about complementary food will cause toddlers to be less nutritionally inappropriate. This study aims to determine the influence of counseling with android application media on the knowledge of toddler mothers about complementary food. This type of research is Reseach and Development (RnD) research with 6 stages that have been carried out by researchers. The sample for the limited-scale test of this study was the mothers of Ujunggede Village toddlers totaling 16 mothers of toddlers in accordance with the criteria of inclusion and exclusion. Normality test results obtained normally distributed data so that for data analysis using paired sample t test. The results of the analysis showed a p value of 0.001 < 0.05. The results of this study show that counseling with the IBBAL MPASI application can increase the knowledge of toddler mothers about complementary food.